Organização dos produtores para a comercialização da laranja: o caso do pool de produtos de Matão-SP. - Castilho, Flaviane Tavanti (Universidade Federal de São Carlos, 2006)
This paper presents a study about a group of orange producers whose purpose is the sale of the production to a processing industry. It is necessary to analyse the strategies adopted by small orange procucers from Matão-SP. The objective is to characterize the performance of this group regarding to the trade of the fruit with the industries. The specific objectives of the research consist in identify the reasons for the group formation and their permanence in the informality, as well as to see if the commercialization of the production made through pool is advantageous to the producers, and to identify how the relations are established among the group during the period of orange production and commercialization. The methodology used was the qualitative research and the case study, and the procedure adopted to the search of the information were interviews with the producers. The hypotesis is that the commercialization of the orange made through pool is more advantageous economically when it is made alone. It was seen that the analysed pool doesn t influence the prices, like that, the organization through pool isn´t advantageous in financial terms, but it presents benefits in terms of behavior, because the producer feels better and safer before industry, because he is delegating to the group leader the function of commercialize his production. Considering the results, it´s possible to say that the hytpotesis was confirmed because the commercialization through pool brings economic advantages to the producer, but benefits him in other aspects like representation and security during negotiation. Key-words: citriculture, pools of producers, small producers, commercialization, action in groups.
Keywords: Organização da produção; Sistema agroindustrial da laranja; Citricultura; Pools de produtores; Pequenos produtores; Comercialização; Ação coletiva; ENGENHARIAS::ENGENHARIA DE PRODUCAO